Molecular damage and lung tumors in cigarette smoke–exposed mice. (24th February 2015) - Izzotti, Alberto; Pulliero, Alessandra
Abstract : Cigarette smoke (CS) induces lung cancer through a multistep process that is now being depicted by molecular analyses. During the early phase (weeks), DNA damage occurs in nuclear and mitochondrial DNA, triggering adaptive responses activated by transient microRNA downregulation in the expression of defensive genes and proteins. During the intermediate phase (months), damaged cells are removed by apoptosis and the resulting cell loss is counteracted by a recruitment of stem cells that are highly sensitive to genotoxic damage. In parallel, microRNA downregulation becomes irreversible because of an accumulation of molecular damage in DICER. During the late phase (years), apoptosis efficacy is decreased by fragile histidine triad loss, while irreversible microRNA downregulation triggers the expression of mutated oncogenes, resulting in adenoma appearance. Furthermore, deletions occur in microRNA‐encoding genes, causing carcinoma formation and uncontrolled growth. All reported pathogenic steps are required to obtain a fully developed lung cancer. This complex pathogenesis develops over a long period of time; therefore, it is difficult to induce cancer in short‐living animals exposed to CS, whereas in humans there is a long latency from the start of smoke exposure to the onset of cancer.